Anxiety and depression in patients with moderate‐to‐severe psoriasis and comparison of change from baseline after treatment with guselkumab vs. adalimumab: results from the Phase 3 VOYAGE 2 study. (18th July 2018) - Gordon, K.B.; Armstrong, A.W.; Han, C.; Foley, P.; Song, M.; Wasfi, Y.; You, Y.; Shen, Y.‐K.; Reich, K.
Abstract: Background: Anxiety and depression are clinically significant comorbidities associated with psoriasis. Improvements in psoriasis are known to decrease anxiety and depression. Guselkumab, an anti‐interleukin‐23 monoclonal antibody, has demonstrated efficacy and safety for the treatment of moderate‐to‐severe psoriasis. Objective: Assess improvements in anxiety and depression with guselkumab vs. placebo and adalimumab using the Hospital Anxiety and Depression Scale (HADS). Methods: In VOYAGE 2, a Phase 3, randomized, double‐blind, placebo‐ and adalimumab‐controlled study, patients received placebo (through week 16 followed by crossover to guselkumab), guselkumab, or adalimumab through week 24. HADS consists of two subscales measuring anxiety (HADS‐A) and depression (HADS‐D), with scores ranging from 0 to 21 and higher scores indicating more severe symptoms. Scores ≥8 indicate instrument‐defined anxiety or depression. Severity of psoriasis was assessed using the Psoriasis Area and Severity Index (PASI). Results: Among 989 patients randomized (with baseline HADS measurements), mean HADS‐A and HADS‐D scores were 6.8 ± 4.2 and 5.3 ± 4.2, respectively; 38.6% of patients reported HADS‐A ≥8 and 27.7% HADS‐D ≥8 at baseline. At week 16, a significantly greater proportion of guselkumab patients with baseline HADS‐A or HADS‐D ≥8 reported HADS‐A <8 (51.4% vs. 25.9%; P < 0.001) or HADS‐D <8 (59.2% vs. 27.0%; P < 0.001) vs. placebo patients. At week 24, a greater proportion of guselkumab patients with baseline HADS‐A or HADS‐D ≥8 reported HADS‐A <8 (58.4% vs. 42.9%; P = 0.028) or HADS‐D <8 (59.8% vs. 46.4%; P = 0.079) vs. adalimumab patients. PASI improvements correlated with improvement in anxiety ( r = 0.27; P < 0.0001) and depression ( r = 0.25; P < 0.0001) scores in patients with baseline HADS‐A or HADS‐D ≥8. Greater improvements in HADS were also observed at week 16 in guselkumab‐treated patients vs. placebo using a more stringent cut‐off of HADS ≥11. Conclusion: Guselkumab treatment was associated with greater improvements in symptoms of anxiety and depression scores in patients with psoriasis compared with placebo and adalimumab.